Is vitamin C able to prevent premature rupture of membranes? - Aryanti, Citra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Premature rupture of membranes (PROM) is leakage of amniotic fluid through ruptured chorioamniotic membranes that occur before starting the labor pain at any gestational age. This is one of the most common problems in obstetrics with many adverse pregnancy outcomes. Main and final mechanisms of membrane rupture is disturbances in its collagen content metabolism. Vitamin C is found to stabilize the cross link triple helix collagen structure and scavange oxidant that involved in PPROM. Association between vitamin C and PROM remained controversial because studies show variaty results. It is important to know the effective dose of vitamin C because giving large doses of vitamin C can cause adverse reactions.